The Effect Of Emotional Intelligence, Team Work, And Organizational Citizenship Behavior (Ocb) On The Performance Of Nurses At Sinar Kasih Toraja Hospital (International Journal of Economics and Management Research, 2026)
This study aims to analyze the influence of Emotional Intelligence, Teamwork, and Organizational Citizenship Behavior on nurse performance at Sinar Kasih Toraja Hospital. The method used is quantitative with data collection through questionnaires to 82 nurses. The data analysis technique uses multiple linear regression through SPSS software version 26. The results of this study were conducted on nurses at Sinar Kasih Toraja Hospital. The sampling technique used is the Slovin technique. The results of the t-test on the Emotional Intelligence variable are 0.008 > 0.05 and the calculated t value is 2.706 <1.99085, on the Team Work variable is 0.001 <0.05 and the calculated t value is 3.516 > t table 1.99085 and on the Organizational Citizenship Behavior variable is 0.000 <0.05 and the calculated t value is 7.107 > t table 1.99085 it can be concluded that Emotional Intelligence, Team Work and Organizational Citizenship Behavior on the performance of nurses at Sinar Kasih Toraja Hospital.